KETERSEDIAAN SARANA DAN PRASARANA PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SAMBAS - Nurul Hidayati E.42008004 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This essay is titled "Availability of Facilities and Infrastructure In Public Service At Population and Civil Registry Ofiice in Sambas Regency ". This writing is supposed to produce a good condition of facilities and infrastructure at the Population and Civil Registry Ofiice in Sambas Regency. This essay is brought up based on the availability of infrastructure and facilities that do not provide comfort to people who are interested in this public service. The conclusion of this research, show that the facilities and infrastructure in Public Service At Population and Civil Registry Ofiice in Sambas Regency are not up to standard, not oriented on the number of users, alot of damage and not prepared, and in filthy conditions and irregular. Facilities and infrastructure that available now cause much discomfort for people with an interest in the Public Service At Population and Civil Registry Ofiice in Sambas Regency. The problem is due to vagueness management infrastructure and the lack of provision of infrastructure and facilities that are not matched by regular maintenance and infrastructure layout irregular.Key Word : Facilities, Infrastructure, and Public Service.